Cooperative Transmission for Multimedia Video Distribution: Models, Algorithms and Implementation - Zhang, Zhaoyu; Wang, Xiaoxue; Sun, Chen; Zhang, Yan (IEEE network, 2025)
In this paper, we introduce cooperative transmission for content distribution in wireless networks. The proposed scheme utilizes the link between User Equipments (UE) to upload data cooperatively and provides a new way of using mobile phones for high-reliability low-latency 4K live video streaming, which can be used in the TV broadcast business. Content from the data acquisition device, such as a professional camera, is split into portions and sent through multiple mobile phones to the aggregation entity where the content is combined. The communication between mobile phones is realized through direct communications. To address common scenarios where both the master UE and the slave UE possess comparable network bandwidth, a static data split strategy is implemented. This strategy involves dividing the data stream equally between the master UE and the slave UE. We carry out experiments with a product prototype in real cellular networks and various scenarios by investigating the bandwidth and latency. The results show that the proposed method can improve the robustness and bandwidth of the 4K video streaming system.